New plant protection partner for southern Africa - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
It was announced at CAB International's triennial Review Conference, held in London in July, that South Africa may shortlybecome a member of CABI. This is good news for southern Africa: Botswana, Kenya, Malawi, Mauritius, Tanzania, Uganda,Zambia...